A REVIEW ON MOSQUITO REPELLENT FINISH FOR TEXTILES USING HERBAL EXTRACTS (International Journal of Engineering Sciences & Management Research, 2015)
Mosquito repellent textiles are one of the most growing ways to advance the textile field by providing the needed characteristics of protecting against mosquitoes, especially in the tropical areas. These types of textiles ensure the protection of human beings from the mosquitoes and the mosquito borne disease includes malaria, filariasis and dengue fever. This study focussed on the penetration of mosquito repellent finish in textile applications as well as nature based alternatives to commercial chemical mosquito repellents in the market. Suitable technologies and materials to achieve mosquito repellency are discussed and pointed out.